Controlled Release of Tramadol from Mixed Matrix Membranes - Donato, L.; Barbaro, G.; Drioli, E.; Algieri, Catia (Journal of Membrane and Separation Technology, 2012)
In this work mixed matrix membranes (zeolite loaded) were prepared and tested as potential devices for the controlled release of tramadol hydrochloride. Due to the hydrophilic nature of the drug, a hydrophobic polymer (polydimethylsiloxane) was chosen for the membrane preparation. NaX zeolites was added to PDMS matrix as modulating agent with the aim to obtain a linear and adequate delivery of the drug in the time as required by the therapeutic needs of this opioid. About the different investigated systems, the PDMS membrane containing 17 wt% of zeolite and 0.2 wt% of drug seems to be the most promising for application as transdermal device. Different mathematical models (Zero order, First order, Higuchi, Bhaskar, and Korsemeyer-Peppas) were used to interpret the drug release mechanism from the different Mixed matrix membranes. The experimental data showed good fit with three different models: Higuchi, Bhaskar and Korsemeyer-Peppas.